Karakterisasi Simplisia dan Ekstrak Kulit Buah Duku (Lansium domesticum Corr) dari Provinsi Sumatera Selatan dan Jambi - Salim, Milana; Sulistyaningrum, Novi; Isnawati, Ani; Sitorus, Hotnida; Yahya, Yahya; Ni'mah, Tanwirotun (Jurnal Kefarmasian Indonesia, 2016)
Duku (Lansium domesticum Corr var duku) is a seasonal native plant from South Sumatra and Jambi. Peel of Duku is useful as botanical insecticide. in South Sumatra and Jambi. The research proves that the skin duku can be useful as an insecticide plant. Quality of compounds in plants can be affected by the origin area of plant, body parts of plants, and extract characters. This study aims to characterize the simplicia and duku peel extract from South Sumatra and Jambi Province. The sample were collected from Simpang Agung Village, OKU Selatan District and Rengas Bandung Village, Muaro Jambi District. The peel was extracted using acetone, while the charactherization based on standardization method from Badan POM Indonesia. Non-Specific parameters which measured were water content, water soluble ash and acid insoluble ash. Specific parameters which measured were water soluble extract, ethanol soluble extract, chromatogram, and chemical compound. Simplicia from Simpang Agung Village contain lower water content, water soluble ash, and acid insoluble ash than simplicia from Rengas Bandung Village. Chromatogram pattern of the peel extract from both village were similar and contain terpenoid and fenolic compound. However hexane yield extract from Simpang Agung Village higher than extract from Rengas Bandung Village therefore contain more insecticides material (terpenoid).